Productive restructuring and labour: the auto industry in Brazil. (1st July 2007) - ,
Abstract : In the early 1980's, Brazilian industry underwent a crisis of the previous accumulation model, ushering in a period in which the country lost international competitiveness. This paper traces the changes that have taken place since then, including the further changes that have taken place since 2003. It concludes that the last four years have not differed much from the earlier pattern, even though several new industrial policies have been introduced with the aim of spurring technological innovation. The paper investigates the reasons for this, seeking to underline the limits and the potentialities of such policies, given the general global context. In order to do so, it analyses managerial strategies and innovative processes in the Brazilian manufacturing sector as a whole, with a special focus on the automotive sector, and discusses the implications of this restructuring for labour.